2021
DOI: 10.1017/s0007114521002932
|View full text |Cite
|
Sign up to set email alerts
|

The association of pre-pregnancy BMI on leptin, ghrelin, adiponectin and insulin-like growth factor-1 in breast milk: a case–control study

Abstract: The nutrient composition of breast milk alters during lactation, and maternal BMI adds more intricacy into its complexity. We aimed to compare leptin, ghrelin, adiponectin, and IGF-1 levels of pre-feed and post-feed breast milk in mothers with obesity and normal weight, and tried to determine their effects on infants’ growth over weight for length z-score. 20 obese and 20 normal weight mothers with 2 month old infants were enrolled in this case-control study. 5 mL pre-feed breast milk and 5 mL post-feed breast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
(51 reference statements)
1
7
1
Order By: Relevance
“…Milk ghrelin was examined in 9 studies (701 dyads) and demonstrated minimal associations with infant growth outcomes. An inverse association was observed with infant weight in 1 study [ 77 ], whereas 5 other studies [ 104 , 51 , 72 , 103 , 58 ] found no association. Positive associations were observed for weight gain in 2 [ 58 , 78 ] of the 5 studies that reported an increased rate of weight gain when higher concentrations of milk ghrelin were present.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Milk ghrelin was examined in 9 studies (701 dyads) and demonstrated minimal associations with infant growth outcomes. An inverse association was observed with infant weight in 1 study [ 77 ], whereas 5 other studies [ 104 , 51 , 72 , 103 , 58 ] found no association. Positive associations were observed for weight gain in 2 [ 58 , 78 ] of the 5 studies that reported an increased rate of weight gain when higher concentrations of milk ghrelin were present.…”
Section: Resultsmentioning
confidence: 90%
“… (+) Association for CDI adiponectin and adiposity (+) Association for CDI skim milk leptin and adiposity (No) Association for HM adiponectin and weight gain. Higher CDI of skim milk leptin was associated with a lower accrual of FFM over 12 mo (−) Association for lactoferrin concentration and visceral depth (+) Association for LActose, total carbohydrates and total protein (intakes) and subcutaneous abdominal fat area (no other significant associations) Fixed effect for infant age and age Interaction with milk component Guler et al.Turkey, 2021 (UMIC) [ 72 ] Cohort 40 2 mo (60 d, SD=10) leptine, ghrelin, adiponectin, IGF-1 (estimated daily intake & concentrations) 2 mo (60 d, SD=10) weight, length, HC, WLZ (WHO standards) (No) Association for Leptin and WLZ at 2 mo (No) Association for ghrelin and WLZ at 2 mo (No) Association for adiponectin and WLZ at 2 mo (No) Association for IGF-1 and WLZ at 2 mo Maternal BMI, age, parity, gestational weight gain and sex Hollanders et al.Netherlands, 2019 (HIC) [ 73 ] Longitudinal 42 30 (±5 d) cortisol, cortisone (concentrations) 1 mo, 2 mo, 3 mo length, weight, BMI, FMI, FFMI, % fat (No) Association for glucocorticoid rhythmicity at 1 mo and body composition or growth at 3 mo HADS-Score, maternal pre-pregnancy BMI, ethnicity, socioeconomic status, gestational weight gain, parity, mode of delivery, mode of HM at 3 mo of age (that is, < or > 80% HM), infant sex, birth weight, gestational age Isganaitis et al.USA, 2019 (HIC) [ 74 ] Longitudinal 37 (31 analyzed at 1 mo, 26 at 6 mo) 1 mo, 6 mo various metabolites (concentrations) 1 mo, 6 mo weight, length, % body fat (that is, fat mass %), total fat mass, total lean mass, trunk fat mass, fat accrual (that is, difference in fat mass from 1 mo to 6 mo) Milk metabolites correlating with weight status at 1 mo : (+) Association for 1-linoleoyl GPE, 2-palmitoyl-GPE, 3-methylxanthine, myo-inositol, pseudouridine, theobromine and weight (−) Association for 1-palmitoylplasmenylethanolamine, 1-stearoyl GPE, 6-sialyl-N-acetllactosamine, acetoacetate, DHA 22:6n:3, guanosine, hexanoylcarnitine C6, nicotinamide, phenylacetylglutamine and weight. Milk metabolites correlating with % body fat at 1 mo : (+) Association for 2-aminobutyrate, 3-methylxanthine, carnitine, cytidine, pseudouridine, theobromine, and % body fat.…”
Section: Resultsmentioning
confidence: 99%
“…The details concerning molecular processes by which maternal milk adipokines contribute to the growth and health of the neonates need to be clarified [57,58]. Milk leptin may act centrally to regulate food intake and also be able to exert effects on the gastrointestinal smooth muscle, thus helping in the creation of a satiety signal and ending breastfeeding [49,[59][60][61][62]. In contrast, adiponectin stimulates food intake, participates in energy balance, and also is involved in lipid and glucose metabolism [49].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, it is believed that the net result of altered adipokine levels in mothers may translate to the offspring's development [15,49,51,62,66,74,75]. It was reported that appetite and satiety regulation are profoundly complex and involve the endocrine and the central nervous system [76,77].…”
Section: Introductionmentioning
confidence: 99%
“…In the context of somatic diseases, hormones, metabolites, cytokines and nutrients are altered, which may implicate an adverse intrauterine environment and affect fetal neurodevelopment (Mac Giollabhui et al ., 2019 ; Nattero-Chavez et al ., 2019 ; Lu-Culligan and Iwasaki, 2020 ). Furthermore, some maternal somatic diseases alter the normal composition of breast milk (Tekin Guler et al ., 2021 ) and severe somatic diseases could influence family environment. These could contribute to the risk of offspring mood/anxiety disorders.…”
Section: Introductionmentioning
confidence: 99%